2014
DOI: 10.1289/ehp.1306755
|View full text |Cite|
|
Sign up to set email alerts
|

Air Pollution and Respiratory Infections during Early Childhood: An Analysis of 10 European Birth Cohorts within the ESCAPE Project

Abstract: Background: Few studies have investigated traffic-related air pollution as a risk factor for respiratory infections during early childhood.Objectives: We aimed to investigate the association between air pollution and pneumonia, croup, and otitis media in 10 European birth cohorts—BAMSE (Sweden), GASPII (Italy), GINIplus and LISAplus (Germany), MAAS (United Kingdom), PIAMA (the Netherlands), and four INMA cohorts (Spain)—and to derive combined effect estimates using meta-analysis.Methods: Parent report of physi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
149
1
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 247 publications
(170 citation statements)
references
References 41 publications
10
149
1
6
Order By: Relevance
“…Modest, but consistent, associations were found between some measures of air pollution and otitis media in a large birth cohort exposed to relatively low levels of ambient air pollution (MacIntyre et al 2011). Consistent evidence was also found for an association between air pollution and pneumonia during early childhood, as well as some evidence for an association with otitis media (MacIntyre et al 2014). Elevated levels of air pollutants increased respiratory tract complaints in children (Altuğ et al 2014).…”
mentioning
confidence: 62%
“…Modest, but consistent, associations were found between some measures of air pollution and otitis media in a large birth cohort exposed to relatively low levels of ambient air pollution (MacIntyre et al 2011). Consistent evidence was also found for an association between air pollution and pneumonia during early childhood, as well as some evidence for an association with otitis media (MacIntyre et al 2014). Elevated levels of air pollutants increased respiratory tract complaints in children (Altuğ et al 2014).…”
mentioning
confidence: 62%
“…Two Canadian papers found the opposite for both cardiovascular and COPD endpoints (Gan et al, 2010;Gan et al, 2013); in their joint models, BC dominated PM 2.5 . Several of the European papers reported significant associations with PM 2.5 , but not with PM abs in single-pollutant models Cesaroni et al, 2014;Fuks et al, 2014;MacIntyre et al, 2014;Pedersen et al, 2013;Raascshou-Nielsen et al, 2013); hence, within Europe the ESCAPE study appears to suggest that PM 2.5 mass is a better indicator of pollution of concern than PM abs . The Canadian studies suggest the opposite.…”
Section: Discussionmentioning
confidence: 99%
“…The ESCAPE studies considered a wide range of health endpoints, including mortality by several cause categories Dimakopoulou et al, 2014;Wang et al, 2014), several morbidity measures MacIntyre et al, 2014;Raaschou-Nielsen et al, 2013;Schikowski et al, 2014;Stafoffia et al, 2014;Fuertes et al, 2014), physiological measures (Fuks et al, 2014;Gehring et al, 2013;Gruzieva et al, 2014), and reproductive measures (Pederen et al, 2013). The results from these studies varied according to the endpoint studied, with cardiovascular endpoints generally showing a significant association with PM 2.5 mass, but not with PM 2.5 absorbance .…”
Section: Epidemiological Studiesmentioning
confidence: 99%
“…First, it is the reduced environmental harm, particularly in terms of a reduction of greenhouse gas emissions, other harmful local air pollutants, traffic noise and the 'urban heat island' effects. As shown by the large-scale European Study of Cohorts for Air Pollution Effects Project in Europe, vehicular traffic gives rise to local air pollutants, notably particulate matters (PM), that contribute to various respiratory and cardiovascular disease incidences, especially among young children (Beelen et al, 2014;Cesaroni et al, 2014;Eeftens et al, 2012aEeftens et al, , 2012bGehring et al, 2013;MacIntyre et al, 2014;Raaschou-Nielsen et al, 2013). Sundvor et al (2012: p. 254) reported that 'the range of the traffic contribution to urban PM concentrations in Europe ranges from 9-53% for PM 10 and 9-66% for PM 2·5 with an average of 39% and 43% at traffic sites, respectively and a higher range for NO 2 of over 80%'.…”
Section: Introductionmentioning
confidence: 99%